To Study the Cadmium Sulphide Thin Films Synthesis by Simple Spin Coating Method for Energy Application - Jagmohan Lal Sharma; S.K. Jain; Balram Tripathi; Mahesh Chandra Mishra (East European Journal of Physics, 2023)
The paper examines the properties of CdS thin film, which is used for window material of solar cells and optical devices. The cadmium sulfide (CdS) thin film was prepared by sol-gel method on glass and ITO substrate. Prepared thin film dried in a vacuum oven at 70℃. Thin film and powder of CdS characterized for structural, optical, and electrical properties by X-ray Diffractometer (XRD), UV-Visible spectrometer, and Keithley spectrometer. The average crystallite sizes, microstrain, and dislocation density of the samples were calculated by the Debye Scherrer formula. The optical band gap of CdS calculated by the Tauc-plot method and obtained 2.40 and 2.41eV for powder and film. The absorption wavelength of CdS is suddenly decreased near 280nm and becomes flat in the higher wavelength region. The FTIR spectrometer is used to identification of unknown materials and bond formation. The bond formation, imperfections, and impurities were observed by the PL spectrometer. Keithley spectrometer is used for I-V characteristics and calculates electrical resistivity by Ohms law.